PSYCHOLOGICAL WELL-BEING AND SMARTPHONE USE AMONG COLLEGE STUDENTS: Received: 28th October 2021; Revised: 14th March 2022, 1st April 2022, 07th May 2022; Accepted: 09th May 2022 - Zheng, Selina (PEOPLE: International Journal of Social Sciences, 2022)
People’s overdependence on smartphones has led them to an abundance of psychological well-being issues. Various literature has examined the association between smartphone use, addictive behaviours, and mental well-being. To develop a deeper understanding of the correlation among these factors, the current study aims to find the psychological impact on smartphone use. Smartphone use and psychological well-being, specifically on how adolescents’ media use has led them to mental health issues such as addiction, depression, anxiety, sleep problems, and the fear of missing out (FoMO). The results supported hypotheses 1, 2, and 3, smartphone addiction correlates with anxiety, depression, and FoMO; however, the results of the study do not support hypothesis 4, in which there is no correlation between smartphone addiction and sleep issues. In conclusion, smartphone overuse and addiction may subsequently affect an adolescent’s mental well-being.